Cystic adenomyosis spreading into subserosal-peduncolated myoma: How to explain it? - Calagna, Gloria (Int J Surg Case Rep, 2015)
INTRODUCTION: Cystic adenomyosis is a rare variant of adenomyosis characterized by well- circumscribed cavitated endometrial gland and stroma located within the myometrium. The cysts usually measure ≥ 1 cm in diameter, contain a “chocolate-colored” fluid and do not open into the overlaying endometrium. CASE PRESENTATION: We present a case of a peduncolated-subserosal cystic adenomyoma, namely cystic adenomyosis, correlated with pelvic MR imaging, laparoscopic surgery technique and histopathology findings. CONCLUSIONS: In this case, the peculiar growth pattern of cystic adenomyosis in a myoma represents a singular condition rarely reported in the medical literature. We therefore support the pathogenetic theory that the disease might have been caused by direct proliferation of endometrial cells within a peduncolated- subserosal myoma.